PENGARUH PEMBERIAN EDUKASI BANTUAN HIDUP DASAR (BHD) TERHADAP PENGETAHUAN MASYARAKAT NELAYAN DALAM PENYELAMATAN KORBAN TENGGELAM DI PESISIR SUNGAI PENITI LUAR KECAMATAN JONGKAT - ida, maulidah; Nadia, Raudatul (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2024)
The rescue of drowning victims is a major challenge for fishermen living on the coast, so health education or education on basic life assistance (BHD) is essential for fishing communities that are highly vulnerable to drownings. The importance of this health education is used to identify early patients with heart attacks and drowning as a link in the chain of care before going to the hospital (pre-hospital). Therefore, fishermen are one of the most important communities for rescuing drowning victims with basic life support. (BLS). Objectives: To know the impact of providing basic life aid education (BHD) on the improvement of the knowledge of the fishing community of Peniti Outdoor Village. Methods: This research method uses a quantitative approach with a pre-test design and a post-test with control group using a pre-experimental design. The sample used 64 respondents, with 32 respondents in the intervention group and 32 respondents in the control group, using total sampling techniques. Results: showed respondents experience improvement (post-test) demonstrated by Wilcoxon statistical test results obtained p value 0,000 (p<0,05). It shows that the provision of basic life assistance education (BHD) has a significant influence on the level of knowledge in fishermen's society. Conclusion: In this study, there is an influence in giving basic life aid education (BHD) on the knowledge of the fishermen community on the banks of the river in the village of Peniti Luar of Jongkat Prefecture